Identifying perinatal depression and anxiety : evidence-based practice in screening, psychosocial assessment and management - Milgrom, Jeannette; Gemmill, Alan (John Wiley & Sons Inc., 2015)
"Identifying Perinatal Depression and Anxiety brings together the very latest research and clinical practice on this topic from around the world in one valuable resource. Examines current screening and management models, particularly those in Australia, England and Wales, Scotland, and the United States. Discusses the evidence, accuracy, and limitations of screening methods in the context of challenges, policy issues, and questions that require further research. Up to date practical guidance of how to screen, assess, diagnose and manage is provided. Considers the importance of screening processes that involve infants and fathers, additional training for health professionals, pathways to care following screening, and the economics of screening. Offers forward-thinking synthesis and analysis of the current state of the field by leading international experts, with the goal of sketching out areas in need of future research"--Provided by publisher.